Systematic Literature Review: Project Management in the VUCA Era and Digital Transformation of Information Systems - Arman Maulana; Siti Rosmayati; Prihartono Aksan Halim Halim (Dinasti Publisher, 2025)
The rapid development of information and communication technology has created new opportunities and challenges for project management, especially in the VUCA environment characterized by volatility, uncertainty, complexity, and ambiguity. This study aims to explore the adaptation of project management in the VUCA era and the impact of digital transformation on information systems. The method used is the Systematic Literature Review (SLR), by reviewing literature from various relevant sources between 2024 and some are targeted to be published in 2025. The results of the study indicate that Agile and Scrum methodologies are the main choices in managing projects in a dynamic environment, while digital transformation, with technologies such as cloud computing and data analytics, increases project efficiency and effectiveness. In addition, the success factors for project implementation in the VUCA era are greatly influenced by innovation, adaptability, proactive risk management, and effective team collaboration. This study concludes that a flexible and innovative project management approach, supported by digital transformation, is essential to facing challenges in the VUCA era, especially in the context of information systems in Indonesia.